Tessier number 30 cleft: report of an antenatally diagnosed case - Kavak, Salih Burcin; Celik, Ebru; Firat, Cemal; Goktolga, Gulser; Ilhan, Rasit; Orak, Ugur (Walter de Gruyter Gmbh, 2014)
Tessier no. 30 cleft, also known as median mandibular cleft or lower midline facial cleft, is extremely rare. Less than 100 cases are reported in the literature, which show great variation in severity and associated abnormalities. We herein report a median mandibular cleft extending into the neck. Its importance comes from the fact that it is one of the two cases diagnosed antenatally and it is the first one diagnosed as early as 17 weeks of gestation. Early diagnosis allowed the patient to deliver in a more specialized clinic that was able to deal with immediate postnatal complications. The family was psychologically prepared for the delivery of a baby with a major anomaly.
Keywords: Antenatal diagnosis; facial cleft; Tessier no. 30